2010
DOI: 10.1111/j.1464-410x.2010.09356.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of palliative transurethral resection of the prostate with disease progression in patients with prostate cancer

Abstract: Objectives To test, in a prostate-cancer population-based database, the validity of the finding that in a single-institution series, palliative transurethral resection of prostate (TURP) is associated with an increased risk of progression. Patients and methods Using the Surveillance and End Epidemiology Registry, we identified men who had a TURP subsequent to their diagnosis of prostate cancer, from 1998 or 1999. The outcome of interest was disease progression, as defined by the initiation of androgen-depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
16
1
1
Order By: Relevance
“…About 9.3% of men with prostate cancer undergo TURP for palliation or for multimodal therapy prior to external beam radiation 29. However, channel TURP is overall associated with worse functional outcomes, treatment failure, and urinary incontinence 30,31.…”
Section: Resultsmentioning
confidence: 99%
“…About 9.3% of men with prostate cancer undergo TURP for palliation or for multimodal therapy prior to external beam radiation 29. However, channel TURP is overall associated with worse functional outcomes, treatment failure, and urinary incontinence 30,31.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that palliative TURP is a safe procedure with acceptable peri‐operative morbidity . Some authors have suggested a negative impact on oncological outcomes , whereas others have reported no impact . From a functional aspect, the risks of postoperative urinary retention, re‐operation, urinary incontinence and long‐term catheterization are markedly high , and are greater in men who have progressed to CRPC .…”
Section: Discussionmentioning
confidence: 99%
“…Palliative transurethral resection of the prostate (TURP) represents the surgical treatment of choice in men with subvesical obstruction and/or recurrent gross hematuria due to locally recurrent CRPC with or without bladder neck infiltration who are not candidates for a radical surgical approach such as salvage RP (SRP) [14,15,16]. It is still discussed controversially if palliative TURP might lead to an accelerated frequency of systemic metastases due to the intraoperative tumor cell shedding, which could result in an increased PCA mortality rate during follow-up.…”
Section: Palliative Transurethral Resection Of the Prostatementioning
confidence: 99%
“…Various groups have described a therapeutic success rate of 70-90% in terms of desobstructing the bladder outlet and prevention of recurrent bleeding and bladder clotting [14,15,16]. About 10% of the patients will need surgical reinterventions due to local recurrences during follow-up.…”
Section: Palliative Transurethral Resection Of the Prostatementioning
confidence: 99%